Cross-Cultural Management Studies: State of the Field in the Four Research Paradigms*. Issue 3 (3rd July 2018) - Romani, Laurence; Barmeyer, Christoph; Primecz, Henriett; Pilhofer, Katharina
Abstract: Cross-cultural management research is often confined to the positivist tradition, which is archetypically illustrated by the seminal work of Hofstede. However, this gives an incomplete overview of the field to which three additional research paradigms contribute: interpretivist, postmodern, and critical. Our ambition is to raise awareness of the presence of multiple paradigms in cross-cultural management research. This meta-theoretical positioning allows researchers to consider the insights and contributions from the different paradigms. We aim to achieve this by presenting a brief overview of the state of the field in each paradigm, thus, stressing areas of studies that enrich our understanding of the interaction between culture and management (at the national, organizational, interpersonal, and individual levels). We then highlight the specific contributions of these four paradigms, drawing especially upon the postmodern and critical works, as they have been repeatedly overlooked in reviews. The article concludes by mentioning how more interactions between the paradigms can be developed and can lead to further knowledge development.